The Determinants of Official OPEC Crude Prices - Verleger, Philip K. (The Review of Economics and Statistics, 1982)
The hypothesis of this paper is that crude oil, like any other unfinished commodity, is valued for the products derived from it; the purpose is to offer an empirical explanation for changes in the crude price charged by the members of OPEC. The model results show that the market-clearing prices reported to prevail for petroleum products on the principal petroleum spot market at Rotterdam are the primary determinants of changes in official crude prices. A systematic relationship between offical and spot prices is argued to have prevailed since 1974. An appendix clarifies five types of data required for the model. 13 references, 4 tables.